The influence of macro- and microelements in seminal plasma on diluted boar sperm quality - Pipan, Maja Zakošek (Acta Vet Scand, 2017)
BACKGROUND: Growing evidence indicates that macro- and microelements in the seminal plasma of humans and various domestic animals are of great importance due to their roles in sperm metabolism, function, survival and oxidative stress. In the present study, we therefore determined the concentrations of macro- and microelements in fresh boar seminal plasma and their relation to sperm quality parameters after 3 days of liquid storage was assessed. Twenty ejaculates from eight boars were collected, and semen volume, concentration, sperm motility, morphology, tail membrane integrity, plasma membrane permeability, mitochondrial membrane potential and DNA fragmentation were determined on the day of collection (day 0) and day 3 (72 h) of storage at 15–17 °C. Seminal plasma was separated and the concentrations of macroelements (Na, K, Ca, and Mg) and microelements (Cu, Fe, Zn and Se) were determined. RESULTS: After 3 days of storage Se levels correlated significantly with sperm motility, progressive motility and morphology, all of which are routinely used for semen evaluation. On day 3, Se levels also correlated with tail membrane integrity, viability and intact DNA (P < 0.05). The correlation coefficients showed that mitochondrial function was better preserved at higher levels of Zn, while higher levels of Cu decreased mitochondrial function, but led to the better preservation of DNA. It was also evident that higher levels of Fe were associated with higher proportions of live spermatozoa and of spermatozoa with normal morphology after 3 days of storage (P < 0.05), while higher levels of Ca and Mg in fresh seminal plasma were associated with lower percentages of progressive motile spermatozoa and with a decreased proportion of spermatozoa with intact DNA (P < 0.05). Multivariate analysis including microelements showed that Se significantly affected sperm quality parameters, mentioned above, after 3 days of storage. CONCLUSIONS: Macro- and microelements were associated with boar sperm quality and may be important biomarkers of boar sperm quality after liquid storage. Our results demonstrate that the evaluation of Se in fresh boar seminal plasma can serve as an additional tool in predicting sperm quality after storage.